2022
DOI: 10.1080/2153599x.2021.2006292
|View full text |Cite
|
Sign up to set email alerts
|

The religiosity gender gap in 14 diverse societies

Abstract: Scholars of religion have long sought to explain the persistent finding that women tend to report greater religiosity than men. However, the size of this 'gender gap' may depend on the measure of religiosity employed, the religious tradition being sampled, and socio-demographic factors.Here, we conduct a systematic cross-cultural investigation into the prevalence of, and explanations for, the religiosity gender gap in 2,002 individuals from 14 diverse societies.While variation exists across societies, women in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…In a large prior meta-analysis of survey studies that included personality and religiosity variables, gender was not found to be a consistent predictor of religiosity (Saroglou, 2010), but our results suggest that this may be truer in Western countries. Cultural context and the type of religious involvement are important in unpacking this question, as seen in the World Values Survey (Sullins, 2006;Vardy et al, 2022). Sullins (2006) reported that the organizational structure of religious institutions can explain why women report less religious involvement in Muslim and Orthodox Jewish contexts, where they are excluded from many practices.…”
Section: Overall Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a large prior meta-analysis of survey studies that included personality and religiosity variables, gender was not found to be a consistent predictor of religiosity (Saroglou, 2010), but our results suggest that this may be truer in Western countries. Cultural context and the type of religious involvement are important in unpacking this question, as seen in the World Values Survey (Sullins, 2006;Vardy et al, 2022). Sullins (2006) reported that the organizational structure of religious institutions can explain why women report less religious involvement in Muslim and Orthodox Jewish contexts, where they are excluded from many practices.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Outside places with exclusionary structures, however, our results match those of many prior studies (e.g., Argyle & Beit-Hallahmi, 2013;Sullins, 2006) in finding that women report higher religious involvement in the countries where a difference is observed. The reasons for this are likely multi-faceted, encompassing aspects of the religious institutions and how participation is constructed, of the presence or lack of other social and economic opportunities, of survey methodology and response patterns (Vardy et al, 2022;Sullins, 2006), and even of the local conceptualization of God (Vardy et al, 2022).…”
Section: Overall Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As religiosity is generally known to be higher in females, both cross-culturally 28 and as reported in ALSPAC specifically 24 , we examined whether these sociodemographic exposures differed by sex, by including an interaction between sex and each exposure. Given that all YPs were approximately the same age (28 years), we did not explore interactions between age and the exposures.…”
Section: Discussionmentioning
confidence: 99%
“…First, this population reflects a very thin slice of human diversity -namely British, predominantly White, and primarily Christian -and patterns reported here may not generalise to other countries, cultures, ethnicities, religions or populations. For instance, although a female RSBB bias is found in many Western, Christian countries, this pattern is not universal, and likely depends on sociodemographic factors, the RSBB measure assessed, and other cultural differences (Vardy et al 2022). Understanding how and why RSBB changes over the lifespan in a diverse range of societies is a key area for future research.…”
Section: Strengths and Limitationsmentioning
confidence: 99%